Risky teaching : harnessing the power of uncertainty in higher education - Roberts, Jay W. (New York, NY : Routledge, 2022)
"Risky Teaching examines the role of risk and uncertainty in teaching and learning in higher education. This book discusses the current landscape of higher education and the challenges and opportunities we face. It synthesizes a range of evidence-based and high-impact practices both in and out of the classroom, offering practical strategies and thought-provoking ideas on educational innovation for students and faculty. Covering topics such as taking risks inside and outside the classroom, staying creative as we grow in our careers, and rethinking assessment, this practical resource is for faculty and instructors to work within and through uncertainty. The book also explores the inward challenges and opportunities associated with risky teaching and how institutional leaders can encourage productive risk taking throughout the organization. This important text is for faculty and instructors in higher education who want to help their students thrive in a complex, unscripted, and disruptive world"--
Part One: Our uncertain world -- Introduction -- Uncertainty in higher education -- Students and uncertainty -- Faculty and uncertainty -- Part Two: Teaching through uncertainty -- The uncertain classroom -- Uncertainty beyond the classroom -- Assessing uncertainty -- Leadership and uncertainty.
Keywords: College teaching; Education, Higher -- Study and teaching; Risk -- Sociological aspects; Educational innovations; EDUCATION / General; EDUCATION / Higher